CLINICAL AND EPIZOOTIC FEATURES OF CATTLE EXTERNAL PARASITOSES’ DEVELOPMENT - Kasianenko, O. I.; Risovaniy, V. I. (Scientific Progress & Innovations, 2021)
Among the urgent problems in the development of modern livestock farming, parasitic diseases play an important role. The article presents the problem of cattle external parasitoses (ectoparasitoses) in Sumy region. According to the Ukrainian and foreign scientists’ viewpoints, the main economic losses caused by ectoparasites are due to a decrease in the average daily weight gain of young animals and insufficient amount of milk during the flight of insects. The aim of our work was to determine the spreading of cattle ectoparasitoses on small farms of Sumy region and establish their clinical and epizootic features. According to the results of the conducted studies, the spreading of hypodermosis and siphunculatosis was revealed, with an average prevalence of 8.20 and 21.69 %, respectively, the diseases were caused by Hypoderma bovis and H. lineatum and Linognathus vituli and Haematopinus eurysternus, respectively. Clinical examination of diseased animals with hypodermosis in the summer revealed eggs of ox warble flies on their hair covering. In places of larvae penetration under the skin, itching, swelling of the subcutaneous tissue, and pain were observed. There was incoordination in some animals. Under the skin along the backbone, nodules were identified. Openings were formed in the center of them - fistulous passages, from which serous, sometimes serouspurulent exudate was released. At siphunculatory invasion, the animals suffered from itching, scratching of the skin, local alopecia, and dermatitis; drops of dried blood were visible on the skin. It should be noted that on small farms of Sumy region, the detected diseases had a pronounced age dynamics. Thus, the largest number of hypodermosis was registered in animals aged from 1 to 2 years, and the lowest (2.17 %) – in young animals up to 1 year of age. At siphunculatoses caused by Linognathus vituli and Haematopinus eurysternus causative agents, young animals under 1 year of age were most often affected, where the prevalence of infection made 33.70 %, and animals older than 5 years were the least affected with an incidence rate of 10.48 %. The obtained data are extremely important in practice, because they allow veterinary medicine practitioners to plan treatment and prevention measures taking into account the peculiarities of the diseases’ development in different age groups of animals.